Use of refrigerated cells for olive cooling and short-term storage: Qualitative effects on extra virgin olive oil. (July 2021) - Guerrini, Lorenzo; Corti, Ferdinando; Cecchi, Lorenzo; Mulinacci, Nadia; Calamai, Luca; Masella, Piernicola; Angeloni, Giulia; Spadi, Agnese; Parenti, Alessandro
Highlights: Cooling slightly increases oxidative processes of olive fruit; Cold storage of olives reduces the production of fusty -related volatile compounds; Cooling of olive fruit can modulate the aroma profile of olive oil; Container type does not affect olive oil quality for short periods of storage. Abstract: In extra virgin olive oil production, the time between olive harvesting and milling is a critical period that must be carefully controlled to preserve oil quality. Particularly, several detrimental phenomena can emerge during storage. Hence, a key issue for producers is to optimize conditions to preserve the quality of fruit before milling. With this requirement in mind, we tested the effect of olive cooling and short-term cold storage on olive oil quality in two experiments. The first, baseline trial was run in the laboratory, and involved storing small batches of olives at 6°C and at 25°C for 16 h. Here, the aim was to simulate a situation with a high temperature difference. The second experiment was conducted at industrial scale, using a refrigerated storage cell. One batch of fruit was stored at 6.5°C for 16–18 h, while a control batch was stored at ambient temperature (13.5 ± 1°C). Finally, the effect of the surface/volume ratio (SVR) of the storage container was evaluated in a full factorial experiment. Although an effect of SVR on olive temperature was found, no significant differences were registered in oil quality. Short-term storage after cooling slowed metabolic processes, reducing hydrolysis of phenols and slowing the development of undesirable compounds. Furthermore, it supported oxidation, evidenced by higher concentrations of the oxidized form of polyphenols and higher production of lipoxygenase pathway compounds. The latter result suggests that this system could be successfully used to modulate the aroma profile of the produced olive oil.